第61次日本南極地域観測隊における宗谷海岸域の地形調査の報告 - 石輪, 健樹; イシワ, タケシゲ; 徳田, 悠希; トクダ, ユウキ; 板木, 拓也; イタキ, タクヤ; 佐々木, 聡史; ササキ, サトシ; Ishiwa, Takeshige; Tokuda, Yuki; Itaki, Takuya; Sasaki, Satoshi (国立極地研究所, 2020)
将来の気候変動に対する南極氷床の応答の理解には，過去の南極氷床変動史の復元およびその変動メカニズムの解明が不可欠である. しかし，地質学的データの時間的・空間的な欠落により南極氷床変動史は十分に復元されていない. 第 61 次日本南極地域観測隊では，活動の一部として宗谷海岸のラングホブデでゾディアックボートを用いた海底地形測量・生物調査・堆積物採取をはじめとする水上調査を展開した. また，ラングホブデ・西オングル島で陸上調査を実施し，表層・陸上堆積物の採取および地中探査レーダーによる地層調査を行った. 取得した海底地形データおよび堆積物は，過去の南極氷床変動史を復元する上で重要な要素となることが期待される. 本報告書では，野外調査の計画および実施内容について報告する. The Antarctic Ice Sheet is a major source of future sea-level rise due to global warming. Reconstruction of the past Antarctic Ice Sheet is essential to understand the mechanism of the Antarctic Ice Sheet response to global and regional climate changes. However, the shortage of geological evidence of sea-level and ice-sheet records makes it difficult to reconstruct the Antarctic Ice Sheet changes. The geomorphological survey is conducted in the 61st Japanese Research Antarctic Research Expedition, and the objective of this survey is to obtain sea-level and ice-sheet records from Lützow-Holm Bay in East Antarctica. We measured the bathymetry and collected sediment samples in shallow water of Langhovde. We also collected the rocks for measuring cosmogenic nuclide and the terrestrial surface sediments, and took an interference pattern under the ground by the ground-penetrating radar in both the Langhovde and West Ongul Island. The data collected will be used to obtain geological evidence of the Antarctic Ice Sheet changes in the future expedition. We report the summary of the geomorphological survey such as planning, logistics, and records. departmental bulletin paper